2016
DOI: 10.1186/s12866-016-0671-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of plasmid-bearing and plasmid-free Chlamydia trachomatis infection among women who visited obstetrics and gynecology clinics in Malaysia

Abstract: BackgroundThe 7.5 kb cryptic plasmid of Chlamydia trachomatis has been shown to be a virulence factor in animal models, but its significance in humans still remains unknown. The aim of this study was to investigate the prevalence and potential involvement of the C. trachomatis cryptic plasmid in causing various clinical manifestations; including infertility, reproductive tract disintegrity, menstrual disorder, and polycystic ovarian syndrome (PCOS) among genital C. trachomatis–infected patients.ResultsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
(40 reference statements)
0
26
2
2
Order By: Relevance
“…It is slightly lower than previous published reports, which showed varied prevalence rates of between 1% and 93.5% [1719]. Discrepancies of the findings in these studies might be due to the fact that almost all of the sub-infertile patients in our study have a regular sexual partner, and were asymptomatic prior to the study.…”
Section: Discussioncontrasting
confidence: 85%
“…It is slightly lower than previous published reports, which showed varied prevalence rates of between 1% and 93.5% [1719]. Discrepancies of the findings in these studies might be due to the fact that almost all of the sub-infertile patients in our study have a regular sexual partner, and were asymptomatic prior to the study.…”
Section: Discussioncontrasting
confidence: 85%
“…Finally, mutant C. muridarum strains that are attenuated in inducing a pathology in the mouse upper genital tract have been identified (57,58), suggesting that these mutants can be safer oral vaccines. However, although attenuated plasmid-free C. trachomatis strains have been identified or created (59)(60)(61)(62)(63)(64)(65), neither their safety nor their efficacy after they are orally taken up into the human GI tract is known.…”
Section: Figmentioning
confidence: 99%
“…Plasmid DNA tends to be present in multiple copies, thus targeting sequences within the plasmid affords a greater sensitivity of detection than chromosomal sites. However, the plasmid is accessory to survival; plasmid-free C. trachomatis isolates have been detected in clinical samples, although they are extremely rare [37,43,44,81,82]. It has previously been suggested that the plasmid might be a poor diagnostic target due to the opportunity for homologous recombination between plasmids and exchange of plasmids between isolates [35]; however, these events are infrequent.…”
Section: Implications On Diagnostic Target Choicementioning
confidence: 99%